Translationfeatures of the words of realities in the poem “To my brother in distance” of Magzhan Zhumabayev (Turkish, Russian and English languages). (Eurasian Journal of Philology Science and Education, 2019)
The article discusses the translation features of the words of realities in the poem “To my brother indistance” of the outstanding Kazakh poet Magzhan Zhumabaev. The author focused on the linguisticand cultural aspect of translating the words of realities into Turkish, Russian, English in this poem, whichwas born at the intersection of romanticism and realism, and is one of the invaluable heritage of nationalliterature. Conclusions are drawn on the basis of the analysis of the translation of words, which, on theone hand, reflect the national color, and on the other, require a special approach to translation. If thetranslation of linguistic and cultural information into other languages and the level of its reception by thereader is one of the topical issues of translation studies, the creativity and translation of Magzhan’s poetrywhich is the culmination apogee of Kazakh symbolism still requires research.The article uses for the first time translations into Turkish and English by Professor of the center forEuropean, Russian and Eurasian studies Timur Kodjaoglu of the University of Michigan and a translationby A. Solovieva in Russian.Despite the fact that a huge number of scientific studies and works in translation studies have beendevoted to the translation of words of national color, various strategies and methods of translation havebeen proposed, the question remains especially debatable among the world’s leading scholars and doesnot have an absolute solution to this day. Words of reality, which play an important role, reflectingthe culture of the people, require a special approach to translation, thereby creating difficulties for the translator. How reflected are they in the translation? If there are changes, then what is their effect? In thisarticle, the author tries to answer these questions.